2021
DOI: 10.3390/cells10061360
|View full text |Cite
|
Sign up to set email alerts
|

Role of 1q21 in Multiple Myeloma: From Pathogenesis to Possible Therapeutic Targets

Abstract: Multiple myeloma (MM) is characterized by an accumulation of malignant plasma cells (PCs) in the bone marrow (BM). The amplification of 1q21 is one of the most common cytogenetic abnormalities occurring in around 40% of de novo patients and 70% of relapsed/refractory MM. Patients with this unfavorable cytogenetic abnormality are considered to be high risk with a poor response to standard therapies. The gene(s) driving amplification of the 1q21 amplicon has not been fully studied. A number of clear candidates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 102 publications
2
21
0
Order By: Relevance
“…+1q is one of the most important chromosomal changes in differing stages of myeloma. From monoclonal gammopathy of undetermined significance, smoldering multiple myeloma, and newly diagnosed MM to relapsed and refractory multiple myeloma, the rate of +1q increases, which implies a relationship between +1q and disease progression ( 11 ), which might be due to the derangement of genes located on 1q21, including MCL-1, IL-6R, and CKS1B, all of which are closely related to myeloma prognosis ( 11 , 12 ). The impact of +1q on the prognosis is still unclear and has not been incorporated into the high-risk factors in most guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…+1q is one of the most important chromosomal changes in differing stages of myeloma. From monoclonal gammopathy of undetermined significance, smoldering multiple myeloma, and newly diagnosed MM to relapsed and refractory multiple myeloma, the rate of +1q increases, which implies a relationship between +1q and disease progression ( 11 ), which might be due to the derangement of genes located on 1q21, including MCL-1, IL-6R, and CKS1B, all of which are closely related to myeloma prognosis ( 11 , 12 ). The impact of +1q on the prognosis is still unclear and has not been incorporated into the high-risk factors in most guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…25 The amplification of 1q21 exists in a certain portion of MM patients, and this unfavorable cytogenetic abnormality has been associated with poor response to standard treatment. 26 The frequency of somatic mutations varies among patients. One study found that KRAS and NRAS mutated exclusively in MM patients, 21.2 and 19.4% in 463 patients, respectively.…”
Section: Genetic Alterationsmentioning
confidence: 99%
“…Other chromosomal abnormalities observed in MM patients include loss of the short arm of chromosome 1 (del(1p)), deletion of the long arm of chromosome 13 (del(13q)), and gain of the long arm of chromosome 1 (gain(1q)) 25 . The amplification of 1q21 exists in a certain portion of MM patients, and this unfavorable cytogenetic abnormality has been associated with poor response to standard treatment 26 …”
Section: Pathogenesis Of Multiple Myelomamentioning
confidence: 99%
“…Some of the 1q21 genes, such as IL6R [ 7 ], ILF2 [ 8 ], MCL-1 [ 9 ], ADAR1 [ 10 ], and CKS1B [ 11 ], were investigated and considered potential drivers of MM development and progression. However, many other candidate genes in this region should also be considered for their role in the pathogenesis, progression, or prognosis of myeloma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%